The (Un)used Opportunities and Benefits of a Person Learning during the Pandemic COVID-19 - Agnieszka Roguska (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction. The pandemic revealed increased on-line activity and thus a greater amount of available training, workshops, and generally materials for self-improvement and others. Research Aim. Paying attention primarily to the potentials and benefits of learning used or likely to be revealed during the COVID-19 pandemic. Evidence-based Facts. The paper refers to the results of research carried out, among others, by: 1) Quality Watch showing the pros and cons of the pandemic, 2) Pomeranian entrepreneurs, pointing to the advantages of switching to the remote work model, and 3) qualitative research in Indonesia with an indication of the advantages of learning based on ICT. The article refers to the third phase of crises described by Gerald Caplan. The third phase is the time of mobilization. Moreover, reference was made to the phenomenon of mental resilience, described in the literature on the subject by Emmy E. Werner. Summary: The article emphasizes the opportunity to look at yourself, to get to know yourself. The disadvantages and inconveniences are listed, but in the context of the possibility of their improvement and elimination on the basis of pandemic experiences. The text draws attention to the value of man as one who strives for balance, uses his internal resources and seeks external help.